Cost of Dyspepsia and Gastroesophageal Reflux Disease in Bangladesh - Aftab, H; Begum, HA; Rahman, M (Journal of Dhaka Medical College, 2010)
Objectives: To estimate the cost of dyspepsia and gastro-oesophageal reflux disease in Bangladeshi patient Methods: A consecutive sample of fifty nine patients attended outpatient clinic of Gastroenterology department of Dhaka Medical College Hospital (June to July 2008) were evaluated using an interview-assisted questionnaires for gastro-oesophageal reflux disease (i.e. heartburn or regurgitation on a weekly basis for at least the past 3 months, and symptom onset at least 12 months prior to the study) or dyspepsia symptom(based on Rome II criteria). The frequency of health resource utilization (i.e. physician visit, hospitalization, laboratory tests, instrumental studies, and medications) and productivity loss (days off work) due to gastro-oesophageal reflux disease or dyspepsia-related symptoms in the past 12 months were recorded. Societal perspective was used, and cost of illness per person per year was estimated in purchasing power parity dollars (PPP$). Results: The cost of illness per person per year for patients with gastro-oesophageal reflux disease, and dyspepsia alone were around PPP$33.29 and PPP$55.35, respectively. There was no statistically significant difference in the cost of illness between the two groups. The direct costs of disease comprised 91.49%and 93.02%of the total costs in gastro-oesophageal reflux disease and dyspepsia patients, respectively with the costs of medications being the dominant component for dyspepsia and investigation cost for gastro-oesophageal reflux disease. Conclusion: Gastro-oesophageal reflux disease and dyspepsia, contribute substantially to the direct costs of medical care in a developing country like Bangladesh. Keywords: Dyspepsia; gastro-oesophageal reflux disease; cost of treatment. DOI: 10.3329/jdmc.v18i2.6266 J Dhaka Med Coll. 2009; 18(2) : 101-104